PERLINDUNGAN HUKUM BAGI PEKERJA NOTARIS/PPAT DALAM PEKERJAANNYA DITINJAU DARI UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - , SERE NELLY YANA, Dr. Ari Hernawan, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to find out about preventive legal protection for workers Notary / Land Deed Officer in doing his job, and resolution taken by workers Notary / Land Deed Officer in terms of their rights as workers are not met. This research is an empirical law of the fieldwork to collect data relating, and normative legal research that examines the law as a norm based research literature. The data were analyzed qualitatively it was presented in the form of a descriptive overview. The result showed that preventive legal protection for workers Notary / PPAT in performing work based employment and labor agreements are made either in writing or orally. The rights and obligations of workers are still not fully implemented in accordance with Act Number 13 of 2003 on Manpower. Rights and obligations of workers who are still not implemented in accordance with the rules, especially in terms of measures of economic, specifically about wages, allowance and severance. Settlement reached in case their rights are not met is the path bipartite seek consensus agreement, if they fail then conducted through the mediation of the dispute settlement rights, conflicts of interest, termination disputes, and disputes between trade unions / labor unions within one company through deliberation mediated by one or more of a neutral mediator.